PENGARUH PENGGUNAAN LEMBAR KERJA SISWA (LKS) BERBASIS SCIENTIFIC EXPLANATION POKOK BAHASAN RANGKAIAN ARUS SEARAH TERHADAP KEMAMPUAN SCIENTIFIC EXPLANATION SISWA DI SMK - Addina Fatikha Zahra; Bambang Supriadi Supriadi; Maryani Maryani (JURNAL PEMBELAJARAN FISIKA, 2019)
For making students’ understanding about content of knowledge can be done byincreasing their scientific explanatory skill, in which this skill can be done throughpractical work. This research is a quasi-experimental research which aims to examinethe effect of worksheets based on scientific explanation on direct current circuitmaterial towards students’ scientific explanatory skill in vocational school. Thisresearch was conducted at the even semester of 2018/2019 academic year in vocationalhigh school 2 Jember grade X DP 1 and X BKP in which each class consisted of 34students. This research was using data collection technique of test and documentation.The data analysis technique itself was using independent sample t-test by the SPSSprogram. The result of the independent sample t-test is the score of the scientificexplanation test was different between the experimental class and the control class.This result showed that there was an effect in the use of worksheets based on scientificexplanation theory on direct current circuit towards students’ scientific explanatoryskill in vocational school.Key word: direct current circuit, students worksheet, scientific explanation.